The hydroxypropyl‐β‐cyclodextrin‐minoxidil inclusion complex improves the cardiovascular and proliferative adverse effects of minoxidil in male rats: Implications in the treatment of alopecia - Fatima Maqoud (Pharmacology Research & Perspectives, 2020)
Abstract The efficacy of minoxidil (MXD) ethanolic solutions (1%‐5% w/v) in the treatment of androgenetic alopecia is limited by adverse reactions. The toxicological effects of repeated topical applications of escalating dose (0.035%‐3.5% w/v) and of single and twice daily doses (3.5% w/v) of a novel hydroxypropyl‐β‐cyclodextrin MXD GEL formulation (MXD/HP‐β‐CD) and a MXD solution were investigated in male rats. The cardiovascular effects were evaluated by telemetric monitoring of ECG and arterial pressure in free‐moving rats. Ultrasonographic evaluation of cardiac morphology and function, and histopathological and biochemical analysis of the tissues, were performed. A pharmacovigilance investigation was undertaken using the EudraVigilance database for the evaluation of the potential cancer‐related effects of topical MXD. Following the application of repeated escalating doses of MXD solution, cardiac hypertrophy, hypotension, enhanced serum natriuretic peptides and K+‐ion levels, serum liver biomarkers, and histological lesions including renal cancer were observed. In addition, the administration of a twice daily dose of MXD solution, at SF rat vs human = 311, caused reductions in the systolic, diastolic, and mean blood pressure of the rats (−30.76 ± 3%, −28.84 ± 4%, and −30.66 ± 5%, respectively, vs the baseline; t test P < .05). These effects were not reversible following washout of the MXD solution. Retrospective investigation showed 32 cases of cancer associated with the use of topical MXD in humans. The rats treated with MXD HP‐β‐CD were less severely affected. MXD causes proliferative adverse effects. The MXD HP‐β‐CD inclusion complex reduces these adverse effects.